Allelopathic Influences of Artemisia Dubia Wall. Ex. Besser on Seed Germination and Seedling Vigor of Parthenium Hysterophorus L - Sharma, Manisha; Devkota, Anjana (Journal of Institute of Science and Technology, 2018)
Allelopathic effect of aqueous (leachate) and solvent extract (hexane, chloroform, methanol and water) of leaf, stem and root of donor plant Artemisia dubia was studied on germination and seedling vigour of Parthenium hysterophorus. Extraction and quantification of different parts in different solvent was done by percolation method. Bioassay was performed by allowing P. hysterophorus seed to germinate in Petri dishes (for solvent, aqueous) in laboratory condition against varied concentrations of prepared extracts of A. dubia. All the tested extract (aqueous, solvent) from different plant parts significantly checked the germination of P. hysterophorus in higher concentration with the effect being more pronounced from the leaf of A. dubia. Linear growth of root and shoot of P. hysterophorus was also checked significantly with increasing concentration of tested plant extract. The order of allelopathic influence was leaf > stem > root in all the cases and it was concentration dependent. Length of root was retarded while stem length experienced no effect, sometime elongation (stem and root extract of leachate, stem extract of hexane and chloroform). These results provide ample evidence that allelopathic potential exist in A. dubia and this can be exploited for the control of P.hysterophorus.Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 127-128